Analisis Potensi Ekonomi Sektor Pariwisata Dan Pengaruhnya Terhadap Pendapatan Asli Daerah Di Provinsi Nusa Tenggara Barat - Musniasih Yuniati; Meiyanti Widyaningrum; Bq Salkiah (KOLONI, 2023)
The Tourism sector is a sector that gives a multiplier effect on economic activities. The purpose of the study is to analyze the economic potential of the tourism sector and determine its effect on original local government revenue in West Nusa Tenggara Province. The research method used is a quantitative research method of multiple regression models with secondary time series data. The results showed the economic potential of the tourism sector related to original local government revenues Income in West Nusa Tenggara is the number of tourist visits and the number of hotels. Multiple regression statistical tests on the variables of the number of tourist visits and the number of hotels show partially and simultaneously the variables of the number of tourist visits and the number of hotels have a significant effect because the significance value (p) < 0.050 on original local government revenues Income in West Nusa Tenggara. Keywords: Economic potential, tourism sector, original local government revenues.